Strategies for Increasing Cultural Communication Competence - Anne Mattina (Academic Chairpersons Conference Proceedings, 2020)
This interactive session will answer the questions: “what happens when we communicate with someone who has a different cultural background than our own?” and, “what can we do to improve the outcomes of those interactions?” Through facilitated discussion and a small group problem-solving exercise, participants will have the opportunity to enhance their current level of cultural awareness, recognize the impact this has on communication competency and improve skills in these areas.
Keywords: communication competence; cultural awareness; intercultural communication; communication skills